The Role of Levetiracetam in Treatment of Seizures in Brain Tumor Patients - Fonkem, Ekokobe; Bricker, Paul; Mungall, Diana; Aceves, Jose; Ebwe, Eromata; Tang, Wei; KIRMANI, BATOOL F. (Frontiers in Neurology, 2013)
Levetiracetam, tradename Keppra, is a new second generation antiepileptic drug that is being used increasingly in brain tumor patients. In patients suffering with brain tumors, seizures are one of the leading neurologic complications seen in more than 30% of patients. Levetiracetam is a pyrollidine-derivative drug, which has a unique mechanism of action. Unlike other antiepileptic drugs, Levetiracetam is proposed to bind to a synaptic vesicle protein inhibiting calcium release. Brain tumor patients are frequently on chemotherapy or other drugs that induce cytochrome P450, causing significant drug interactions. However, levetiracetam does not induce the P450 system and does not exhibit any relevant drug interactions. Intravenous delivery is as bioavailable as the oral medication allowing it to be used in emergency situations. Levetiracetam is an attractive option for brain tumor patients suffering from seizures, but also can be used prophylactically in patients with brain tumors or patients undergoing neurological surgery. Emerging studies have also demonstrated that levetiracetam can increase the sensitivity of Glioblastoma tumors to the chemotherapy drug Temozolomide. Levetiracetam is a safe alternative to conventional Antiepileptic drugs and an emerging tool for brain tumor patients combating seizures.